Time-resolved optically stimulated luminescence of quartz in the nanosecond time domain - Schmidt, Christoph; Simmank, Oliver; Kreutzer, Sebastian (Journal of luminescence, 2019)
Time-resolved optically stimulated luminescence (TR-OSL) is one of the few methods to characterise the type of recombination centre involved in luminescence production and its response to thermal, optical and irradiation treatments. TR-OSL experiments for natural quartz yielded lifetimes mainly in the range 30–45 μs, often supplemented by shorter or longer values in the μs range. For distinct types of bedrock quartz and K-feldspar much shorter lifetimes in the ns range have been reported. Here we further explore the characteristics of this short lifetime component in quartz and look for links to specific components in the quartz OSL signal with emphasis on the slow component. Our experiments were carried out on a newly developed measurement system available as an attachment to Freiberg Instruments lexsyg research readers that allows recoding TR-OSL signals with a minimum dwell time of 2.5 ns. We demonstrate that all of the nine investigated natural quartz samples give rise to a short lifetime component in the range 30–200 ns, which does not originate from measurement artefacts or feldspar contaminants. For most samples, two further lifetimes of 0.7–3.2 μs and 39–160 μs accompany this component as indicated by multi-exponential curve fitting. Our results show that the short lifetime component does not change substantially with annealing up to 500°C, whereas it appears to rise slightly with irradiation up to a dose of 200–800Gy. The process behind the decrease of the short lifetime component down to ∼30 ns with measurement temperature up to 110°C could not be certainly identified. With the measurement data compiled so far, we presently cannot establish a link between the short lifetime component and the OSL slow component.